Molecular Characterization of Glossiphonia elegans (Verrill, 1872) (Glossiphoniidae: Hirudinida) from its type locality, West River, New Haven County, Connecticut, USA - Moser, William E.; Richardson, Dennis J.; Hammond, Charlotte I.; Lazo-Wasem, Eric (Zootaxa, 2012)
Clepsine elegans Verrill, 1872 was described based on material collected from the West River, New Haven, New Haven County, Connecticut, USA (Verrill, 1872). Moore (1901) synonymized C. elegans with the European congener Glossiphonia complanata (Linnaeus, 1758) in view of the morphological similarities of the two species. Subsequently, all North American leeches bearing 6 eyespots and a pair of paramedial lines were considered Glossiphonia complanata. Using specimens collected from Ontario and Michigan, Siddall et al. (2005) resurrected Glossiphonia elgans (Verrill, 1872), because specimens collected from Ontario, Canada and Michigan, USA showed considerable genetic distinction from, and did not form monophyletic group with, European specimens of G. complanata.